Religious disparities in health in Bangladesh–the case of hypertension and diabetes: evidence from two nationally representative cross-sectional surveys - Nurul Alam; M Moinuddin Haider; Md Mahabubur Rahman; Nahid Kamal; Mamun Ibn Bashar; Shusmita Hossain Khan (BMJ Open)
Objectives Religious affiliation, beliefs, and practices shape lifestyles and disease risks. This study examined Hindu–Muslim differences in the prevalence and management of hypertension and diabetes in Bangladesh, a religiously plural country with 91% Muslims and 8% Hindus.Design, settings and participants We used the nationally representative 2011 Bangladesh Demographic and Health Survey (BDHS) and 2017–2018 BDHS data. The 2011 BDHS collected blood pressure (BP) data with an 89% response rate (RR) and fasting blood glucose (FBG) data (RR 85%) from household members aged 35 years and above. The 2017–2018 BDHS collected BP and FBG data from household members aged 18 years and above with 89% and 84% RRs, respectively. We analysed 6628 participants for hypertension and 6370 participants for diabetes from the 2011 BDHS, 11 449 for hypertension and 10 744 for diabetes from the 2017–2018 BDHS.Methods We followed the WHO guidelines to define hypertension and diabetes. We used descriptive statistics and multiple logistic regression to examine the Hindu–Muslim differences in hypertension and diabetes, and estimated predicted probabilities to examine the changes in hypertension and diabetes risk over time.Results Nine in 10 of the sample were Muslims. About 31% of Hindus and 24% of Muslims were hypertensive; 10% of both Hindus and Muslims were diabetic in 2017–2018. The odds of being hypertensive were 45% higher among Hindus than Muslims (adjusted OR: 1.45; 95% CI: 1.23 to 1.71; p<0.001). The levels of awareness, medication and control of hypertension were similar between the religious groups. Between the 2011 and 2017–2018 BDHS, the Hindu–Muslim difference in the prevalence of hypertension increased non-significantly, by 3 percentage points.Conclusions Further studies on religious-based lifestyles, Hindu–Muslim differences in diet, physical activity, stress, and other risk factors of hypertension and diabetes are needed to understand Hindus’ higher likelihood of being hypertensive, in contrast, not diabetic compared with Muslims.